Is the Sinaloa Cartel a Mafia? - Paoli, Letizia (The British journal of criminology, 2024)
Aiming to reduce the conceptual ambiguity surrounding the topic of organized crime, this study assesses the extent to which the Sinaloa Cartel, the most prominent Mexican drug syndicate, has the characteristics of a mafia. The study uses Paoli’s 2020 mafia framework, which identifies seven typifying characteristics of mafias, such as the Sicilian Cosa Nostra or the Japanese Yakuza. It relies on a broad review of the literature, court transcripts and media sources. The Sinaloa Cartel fully meets none of the seven typifying traits of mafias. It comes closest on the last trait, popular legitimacy and power-sharing, but it is properly characterized as a large drug-selling enterprise. Lastly, the study draws (sombre) policy implications from the analysis.